2022
DOI: 10.3389/fpls.2022.1006835
|View full text |Cite
|
Sign up to set email alerts
|

Xylem anatomy and hydraulic traits in Vitis grafted cuttings in view of their impact on the young grapevine decline

Abstract: Grapevine grafting is an essential practice in viticulture and over the years, various bench grafting techniques have been developed to mechanize the nursery process and to increase the yield in number of viable cuttings. Bench grafting is a fundamental nursery practice that can potentially affect the quality of propagation material also in young decline associated to grapevine trunk diseases and has been recently reported to influence leaf symptoms development associated with diseases of Esca complex. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In V. vinifera, a species with creeping habit, pruning wounds do not heal as in fruit trees, where the stem cambium usually develops new tissues such as callose (Nakashima et al, 2003;Câmpu, 2009;Grünwald et al, 2002;Battiston et al, 2022). Neither does the plant produce suberin in comparison to other trees (Rittinger et al, 1987;Hawkins and Boudet, 1996) to protect the internal living tissues against the external environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In V. vinifera, a species with creeping habit, pruning wounds do not heal as in fruit trees, where the stem cambium usually develops new tissues such as callose (Nakashima et al, 2003;Câmpu, 2009;Grünwald et al, 2002;Battiston et al, 2022). Neither does the plant produce suberin in comparison to other trees (Rittinger et al, 1987;Hawkins and Boudet, 1996) to protect the internal living tissues against the external environment.…”
Section: Discussionmentioning
confidence: 99%
“…Samplings were carried out either on the same day as pruning (experimental control, T0); or aft er 1 (T1), 2 (T2), or 9 (T9) months aft er pruning. Th ree replicates from different plants (biologically independent) were examined at each sampling time (n = 3), following the methods described by Battiston et al (2022). For each of the four pruning methods (described above), at T0 and T1 the percentages of stem vessels occluded by tyloses were recorded, at T2, light microscopy observations of histological responses were carried out, and at T9, the desiccation areas below the wounds were described.…”
Section: Pruning Methods Sampling and Trial Set-upmentioning
confidence: 99%
“…In addition, in small vessel-cultivars, the ease of occluding the vasculature could favour the physical compartmentalization of fungi ( Pouzoulet et al., 2014 ; Pouzoulet et al., 2020a ). A recent study showed that in the nursery, three different grafting techniques adopted on three different V. vinifera varieties onto the same rootstock (Kober 5BB) allowed diverse levels of callus formation and vascularization of the grafting point ( Battiston et al., 2022 ). Such results confirm the influence of the genotype on wood formation and response to pathogens.…”
Section: Transcriptional Reprogramming Hormonal Crosstalk and Specifi...mentioning
confidence: 99%